Performance analysis of signal-to-noise ratio estimators in AWGN and fading channels - Gopal, Lenin; Sim, M.L. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Additive White Gaussian Noise (AWGN) and Rayleigh fading severely degrade the performance of the wireless communication systems. Most of the wireless communication systems require knowledge of the channel Signal-to-Noise ratio. In this paper a few methods are proposed to estimate the SNR in the presence of AWGN and Rayleigh fading. The mean square error (MSE) and root mean square error (RMSE) are used as performance measures. Simulation result shows that the newly proposed estimators mlfad can provide better performance in most circumstances under AWGN and Rayleigh fading channels.